Community Language Learning as a Supportive Approach to Affect EFL Learners’ Speaking Skills - Ramli, Ramli; Nurhidayati, Nurhidayati; Arifin, Arifin; Rafiqa, Syarifa; Rosmayanti, Vivit; Kusmaryani, Woro (Linguistics and ELT Journal, 2025)
This study examined the effectiveness of the Community Language Learning (CLL) method in enhancing the speaking skills of seventh-grade students at SMPN 11 Tarakan. Speaking ability is widely acknowledged as a fundamental component of effective communication in both academic and professional contexts; however, it is often regarded as the most challenging language skill to develop due to affective barriers such as anxiety, low self-confidence, and limited vocabulary. The CLL method was selected as an instructional intervention because it emphasizes collaboration, a sense of community, and learner-centered interaction within a supportive learning environment. Using a pre-experimental one-group pretest–posttest design, the study involved 29 students from class VII-2. The findings revealed a statistically significant improvement in students’ speaking performance following the implementation of the CLL method. Specifically, the mean speaking score increased from 38.62 in the pretest to 63.45 in the posttest, indicating that the Community Language Learning method was effective in improving the speaking skills of seventh-grade students.